Compact Vitis vinifera-Inspired Ultrawideband Antenna for High-Speed Communications - Jeremiah O. Abolade; Dominic B. O. Konditi; Vasant M. Dharmadhikary (International Journal of Antennas and Propagation)
A new compact ultrawideband (UWB) bioinspired antenna is presented in this work. The proposed antenna consists of a vine leaf (Vitis vinifera) shape as the radiating patch, defected ground structure (DGS), and a vertical rectangular slot (VRS) on the ground plane. The vine leaf shape is realized from a circular patch (initiator) in this work. The proposed antenna is built on an FR4 substrate with a dielectric constant of 4.4, a loss tangent of 0.02, and a thickness of 1.5 mm. The total dimension of the proposed bioinspired antenna is 35 × 27.6 mm2. The proposed antenna has a fractional bandwidth of 115.43% (3.7 GHz–13.8 GHz) at 10 dB return loss, a radiation efficiency between 78% and 97%, a peak gain of 6.7 dB, and a stable radiation pattern. The contributions of this work to the existing literature are as follows: (i) the investigation of a vine leaf shape for UWB antenna application; (ii) the adaptation of the conventional monopole patch antenna design equation to determine the lower edge frequency (LEF) of an arbitrary shape monopole antenna; (iii) the presentation of a compact UWB antenna with high fractional bandwidth compared with recent works in the literature, and (iv) the use of FR4 substrate to achieve a peak radiation efficiency of 97% with a compact structure.